THE INFLUENCE OF DIGITAL MARKETING, BRAND AMBASSADOR, AND ONLINE CUSTOMER REVIEW ON THE PURCHASE DECISION OF SCARLETT WHITENING SKINCARE PRODUCTS ON THE SHOP E-COMMERCE PLATFORM - Eka Syafitri, Olivia; Santi Hariyani, Diyah; Apriyanti (Universitas Tulungagung, 2024)
This study aims to determine the influence of digital marketing, brand ambassadors, and online customer reviews on purchasing decisions for Scarlett Whitening Skincare products on the Shopee E-Commerce Platform in Madiun City. The type of research used in this study is a quantitative approach, while the analysis tool used is SPSS version 25. Sampling in this study used Purposive Sampling. The sample used was 385 respondents. Statistical testing results show that digital marketing positively and significantly affects purchasing decisions for Scarlett Whitening skincare products on the Shopee e-commerce platform. 2) Brand ambassadors positively and significantly affect purchasing decisions for Scarlett Whitening skincare products on the Shopee e-commerce platform. 3) Online customer reviews positively and significantly affect purchasing decisions for Scarlett Whitening skincare products on the Shopee e-commerce platform.